Breast cancer detected as an incidental finding on 99mTc-MIBI scintigraphy. (July 2017) - Homma, Toshihiro; Manabe, Osamu; Ichinokawa, Kazuomi; Yamashita, Hiroko; Oyama-Manabe, Noriko; Kato, Fumi; Hirata, Kenji; Kroenke, Markus; Tamaki, Nagara
We report a case of breast cancer detected as an incidental finding on 99m Tc-MIBI scintigraphy. 99m Tc-MIBI scintigraphy is usually used to evaluate cardiac perfusion or to detect ectopic parathyroid adenomas; however, it is also known to sensitively detect breast cancer. Accordingly, a few reports have described the incidental detection of breast cancer by 99m Tc-MIBI scintigraphy performed to detect parathyroid adenoma. Our present case underscores the importance of attending to any incidental findings when searching for parathyroid adenomas using 99m Tc-MIBI scintigraphy.